Exploring disease parameters and clinical outcomes in pyogenic liver abscess in a tertiary center in Chitwan - Bhujel, Sushim; timilsina, Binay; Pradhan, Saroj Babu; Khatiwada, Sagar; shrestha , Sandesh; Belbase, Narayan Prasad (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Pyogenic liver abscess (PLA) remains a clinically significant condition, despite advancements in imaging, microbiology, and minimally invasive interventions, challenges persist due to variable pathogens, rising antibiotic resistance, and various treatment modalities. The study was conducted to characterize disease parameters and treatment outcomes of PLA in patients presenting to a tertiary center in Chitwan, Nepal.Methods: A retrospective observational study was conducted at College of Medical Sciences Teaching Hospital, Bharatpur, Nepal, analyzing patients diagnosed with PLA from November 1, 2021 to October 31, 2024. Data were collected on demographics, clinical presentations, laboratory findings, microbiological isolates, radiological characteristics, and treatment modalities.Results: A total of 34 patients were included, with a mean age of 65.06±16 years and a male predominance 25(73.53%). The right hepatic lobe was involved in 23(67.6%) of cases, left-lobe in 7(20.6%) and both lobes in 4(11.8%). Microbiological cultures were positive in 21(55.9%) of cases, with Klebsiella pneumoniae 7(20.58%), followed by Escherichia coli 4(11.76%) and Bacteroides spp 2(2.94%), suggesting an enterobiliary source in select cases. Antibiotic therapy alone was successful in 6(17.6%) of cases. Percutaneous image-guided drainage was performed in 14(41.2%) of cases, while surgical intervention was required in 14(41.2%) laparoscopic drainage: 8(23.5%), open surgical drainage: 6(17.6%).Conclusions: Percutaneous drainage remains the preferred initial approach. However, a significant proportion of patients with multiloculated abscesses, high-viscosity pus, or failed radiological drainage required surgical intervention.